Methodological Fundamentals of Teaching and Learning Classical and Modem Languages - Morkevičienė, Sigita (Acta Paedagogica Vilnensia, 2002)
The article deals with methodological problems of Classical languages teaching and learning. Theoretical investigation proves the peculiarities of Latin and Old Greek in contemporary education, emphasizing the importance of these languages on the development of European cultural values. Research aim is to investigate teaching and learning theoretical aspects of Modem and Classical languages, showing changes taking place during their instruction. Research object is basics of Classical languages teaching and learning. Research method implies theoretical analyses of scientific literature. Methodological foundation of the research is based on positivistic attitude which emphasizes conscious process of cognition. Special attention is focused on historical introspection of Latin and Old Greek teaching methods. The author also provides up-to-date information on second language acquisition theories in respect of learning languages. Besides the paper aims at analysing modern language teachers' works concerning conscious learning and reasonable active teaching. Thus, one should educate such factors of mental activity as cognition, capability and resolution in perfect harmony with the whole formation of ones' personality. The new attitude towards Classical languages teaching and learning has to contribute towards the conscious development of creative man.
Keywords: Teaching; learning; methodological problems; classical languages; Latin; Old Greek.